Dissemination Models for Communication of Cultural Heritage: ‘di sotto in su’ Perspective Domes in Andrea Pozzo’s Work - Leonardo Baglioni; Marta Salvatore (Diségno)
This research deals with the communication and enhancement of cultural heritage through the construction of physical models that reproduce abstract theoretical processes making them accessible through visual interactive experience. This type of experimentation concerns perspective, in particular, the perspectives of fake hemispherical domes defined ‘di sotto in su’ (from below) painted by Andrea Pozzo between the Seventeenth and Eighteenth centuries. The present essay explores the relationship between the true form of the dome and its perspective, with particular reference to the case of St. Ignatius, through the development of a theory that leads the different perspective images of the dome to a single ideal design model. This hypothesis has been analytically verified by measuring the invariance of the cross-ratio between the principal elements of the architectural order that articulate the tambour of the dome. This experimentation has been reproduced in an installation that relates the physical model of the true form of the dome with its perspective images and with the observer. The installation, which shows and demonstrates perspective through the perspective itself, has two distinct aims: the experimental validation of the formulated hypotheses and their subsequent sharing.